Interventions and solutions for water supply on small islands: The case of New Providence, The Bahamas - Welsh, Kristen; Bowleg, John (Frontiers in Water, 2022)
Small island nations make up more than one-quarter of the countries on earth, yet information on the limitations of the hydrologic cycle in small islands and strategies to address freshwater availability are lacking. Typically, all islands are characterized by their limited supply of freshwater, and their governments commonly rely on large-scale interventions to provide residents with potable water. The island of New Providence in The Bahamas is home to the capital city of Nassau and almost three-quarters of the country’s population. New Providence has a long history of hydrologic interventions to supply domestic and industrial water. Historic groundwater sources have been over-extracted to severe levels of salinization, and some groundwater aquifers have not recovered after more than eighty years later. Fresh water was barged in from the larger Andros Island for approximately forty years, which ultimately became insufficient to meet demand on New Providence. In addition to an aggressive Non-Revenue-Water (NRW) Program, desalinization of ocean water via diesel-operated reverse osmosis plants has served as the primary source of potable water for the island. Present concerns have grown due to its contributions to greenhouse gas emissions. The Bahamas is also investigating alternative mechanisms for providing clean drinking water to the country, with Ocean Thermal Energy Conversion (OTEC) under consideration to co-generate clean energy in addition to drinking water. This article reveals that historic interventions to source drinking water for New Providence Island have proven to be unsustainable and ultimately have threatened the freshwater availability. Current efforts to investigate drinking water provision through OTEC are promising, particularly for the potential co-generation of energy and to promote sustainable development. This solution may be promising for other small islands where development is often challenged by water availability and sustainable energy provision.